An Analysis of the Role of Village Owned Enterprises (BUMDes) in Improving Community Welfare in Harapan Village, Tanete Riaja Subdistrict, Barru Regency - A.Aminah; Dian Pratiwi (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal